2001
DOI: 10.1242/jcs.114.21.3915
|View full text |Cite
|
Sign up to set email alerts
|

External alternative NADH:ubiquinone oxidoreductase redirected to the internal face of the mitochondrial inner membrane rescues complex I deficiency inYarrowia lipolytica

Abstract: Alternative NADH:ubiquinone oxidoreductases are single subunit enzymes capable of transferring electrons from NADH to ubiquinone without contributing to the proton gradient across the respiratory membrane. The obligately aerobic yeast Yarrowia lipolytica has only one such enzyme, encoded by the NDH2 gene and located on the external face of the mitochondrial inner membrane. In sharp contrast to ndh2 deletions, deficiencies in nuclear genes for central subunits of proton pumping NADH:ubiquinone oxidoreductases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…We found that AOX loss is always related to CI loss (preceding it in 4/6 events), whereas NDH2 duplication is associated with CI loss (preceding 3/6 events) in all but S. bacillaris . This suggests that the ancestral species that lost CI already lacked AOX and had increased alternative NDH2 activity (which could have compensated loss of CI function, as previously described [10,11,56]). In S. bacillaris , the increase in mitochondrial NDH2 activity may be mediated through the expanded, mitochondrially retargeted, NADH oxidase family (figure 2 e ).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…We found that AOX loss is always related to CI loss (preceding it in 4/6 events), whereas NDH2 duplication is associated with CI loss (preceding 3/6 events) in all but S. bacillaris . This suggests that the ancestral species that lost CI already lacked AOX and had increased alternative NDH2 activity (which could have compensated loss of CI function, as previously described [10,11,56]). In S. bacillaris , the increase in mitochondrial NDH2 activity may be mediated through the expanded, mitochondrially retargeted, NADH oxidase family (figure 2 e ).…”
Section: Resultssupporting
confidence: 59%
“…royalsocietypublishing.org/journal/rsob Open Biol. 11: 200362 lacked AOX and had increased alternative NDH2 activity (which could have compensated loss of CI function, as previously described [10,11,56]). In S. bacillaris, the increase in mitochondrial NDH2 activity may be mediated through the expanded, mitochondrially retargeted, NADH oxidase family (figure 2e).…”
Section: Comparing Signatures Of Recent and Ancient Complex I Losssupporting
confidence: 57%
See 1 more Smart Citation
“…NDH-2 performs the same catalytic function as respiratory complex I, and its expression was observed to restore the mitochondrial activity in yeast and animals with complex I deficiency. , Therefore, NDH-2 has attracted interest as a key enzyme for the treatment of complex I-related neurodegenerative disorders like Parkinson’s disease . In addition, NDH-2 is the only enzyme with NADH:quinone oxidoreductase activity expressed in many pathogenic organisms, and for that, it has been proposed as a possible new drug target for the rational design of antibiotics. …”
mentioning
confidence: 99%